2019
DOI: 10.3390/genes10100833
|View full text |Cite
|
Sign up to set email alerts
|

Likely Pathogenic Variants in One Third of Non-Syndromic Discontinuous Cleft Lip and Palate Patients

Abstract: Oral clefts are composed of cleft of the lip, cleft of the lip and palate, or cleft of the palate, and they are associated with a wide range of expression and severity. When cleft of the palate is associated with cleft of the lip with preservation of the primary palate, it defines an atypical phenotype called discontinuous cleft. Although this phenotype may represent 5% of clefts of the lip and/or palate (CLP), it is rarely specifically referred to and its pathophysiology is unknown. We conducted whole exome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…We also identified a novel missense variant in DLG1 (NM_001366207.1: c.175A > G; NP_001353136.1: p.Thr59Ala) in Family 17. Common variants in DLG1 have been associated with an increased risk for non‐syndromic OFCs (Mostowska et al, 2018) and a novel nonsense variant in DLG1 was previously found in an individual with non‐syndromic discontinuous CLP (Demeer et al, 2019). Lastly, we identified a missense variant of interest in MYH9 in Family 22 (NM_002473.6: c.4745A > G; NP_002464.1: p.Glu1582Gly).…”
Section: Resultsmentioning
confidence: 99%
“…We also identified a novel missense variant in DLG1 (NM_001366207.1: c.175A > G; NP_001353136.1: p.Thr59Ala) in Family 17. Common variants in DLG1 have been associated with an increased risk for non‐syndromic OFCs (Mostowska et al, 2018) and a novel nonsense variant in DLG1 was previously found in an individual with non‐syndromic discontinuous CLP (Demeer et al, 2019). Lastly, we identified a missense variant of interest in MYH9 in Family 22 (NM_002473.6: c.4745A > G; NP_002464.1: p.Glu1582Gly).…”
Section: Resultsmentioning
confidence: 99%
“…FZD1 and its receptor are expressed ventral to the telencephalon and in periocular mesenchyme during the development of the face [ 31 ]. Loss of function variants in DLG1 are associated with non-syndromic discontinuous cleft lip and palate [ 32 ]. MMP25 expression appears to have a crucial role throughout all stages of palatal development [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, no syndrome caused by germline ARHGAP29 mutations has so far been reported. This is in contrast to several other NsCL/P genes as causative likely pathogenic variants can be identi ed in about 10% of NsCL/P cases in the genes causing SyCL/P [6,38,39]. ARHGAP29 should thus be included in diagnostic genetic testing for NsCL/P, as it may be mutated in around 2% of patients with high penetrance.…”
Section: Discussionmentioning
confidence: 99%